Application of 3D Printed Porous Copper Anode in Microbial Fuel Cells - Bian, Bin; Wang, Chunguang; Hu, Mingjun; Yang, Zhaoliang; Cai, Xiaobing; Shi, Dai; Yang, Jun (Frontiers in Energy Research, 2018)
In this study, 3D printing technique was utilized to fabricate three-dimensional porous electrodes for microbial fuel cells with UV curable resin, followed by copper electroless plating. A maximum voltage of 62.9 ± 2.5 mV and a power density of 6.45 ± 0.5 mWm−2 were achieved for MFCs with 3D printed porous copper (3D-PPC) anodes, which were 8.3- and 12.3-fold higher than copper mesh electrodes, respectively. This illustrated the great advantage of 3D porous anodes in MFCs compared to flat anode structures. Besides, the biocompatibility of the copper anode with Shewanella oneidensis MR-1 was examined by comparing with carbon cloth, which produced a 3-fold larger maximum voltage and a 10-fold higher power density vs. 3D-PPC anodes and thus indicated the possible copper corrosion during MFC operation. ICP-MS analysis of MFC solution revealed the high concentration of 732 ± 27.1 μg/L copper ions detected in the MFC effluent. This result, coupled with EDX showing the lower copper content on the 3D-PPC anode surface after >15 days of MFC operation, confirmed the copper dissolving behavior in MFC. MR-1 biofilm formation under copper suppression was finally characterized by SEM and less biofilm was observed on copper anodes, illustrating their poor biocompatibility, even though 3D printing technology and porous structures were quite promising for future scale-up.